Edukasi Masa Depanku, Pilihanku: Menumbuhkan Growth Mindset dan Kesadaran Bijak dalam Menghindari Pernikahan Dini pada MA Daarul Hasan Desa Cihawuk: Pengabdian - Dzulfikar Maulana Rahadian PM; Sani Asmi Ramdani Lestari; Allysa Angraeni; Syifa Abdillah; Alfani Yunisa; Rofita Alya Puspita Sari; Regitha Anggraeni Koswara Putri; Muhammad Hamiz Al-Qowiyy; Luthfi Roja Wirawan; Dinda Thalia Trianita Putri; Muhammad Rafi Ghani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Early marriage remains a worrying social issue in Indonesia, especially among teenagers. Cihawuk Village, Bandung Regency, is one of the areas with a high tendency of early marriage due to educational, economic, cultural, family, and promiscuity factors. A community service program entitled "My Future, My Choice" was implemented to foster a growth mindset and wise awareness in avoiding early marriage through an interactive educational approach. This study used a quantitative method with a one-group pretest-posttest design on 30 students of MA Daarul Hasan, Cihawuk Village, aged 17–18 years. A Likert scale questionnaire was used to measure indicators of growth mindset and reflective awareness of the impact of early marriage. Analysis was carried out descriptively using Microsoft Excel. The results of the community service showed no significant difference between the pre-test (total score of 2.8 out of 4) and post-test (score of 2.8 out of 4). There was a decrease in the percentage of perception levels in the post-test on the aspects of growth mindset (Δ mean = -0.3), fixed mindset ((Δ mean = -0.14)), and early marriage hinders ideals (Δ mean = -0.06), but there was an increase in knowledge on the aspects of marriage not as an economic solution (Δ mean = +0.2) and the future depends on current choices (Δ mean = +0.2). Although the aspects of growth mindset and fixed mindset did not yield the expected results, education on preventing early marriage